Simulation study of convex corner undercutting in KOH and TMAH for a MEMS piezoresistive accelerometer - Yusof, N.; Soin, N.; Noorakma, A.C.W. (Penerbit UTM Press, 2016)
Undercutting is a common problem in wet anisotropic etching. This problem in turn, influences the performance and sensitivity of MEMS devices. This paper investigates the use of corner compensation to prevent convex corner undercutting in a MEMS piezoresistive accelerometer. The Intellisuite CAD simulation software was used for designing the mask with corner compensation and for analysing wet anisotropic etching profiles in potassium hydroxide (KOH) and tetra-methyl-ammonium-hydroxide (TMAH) solutions at different concentrations and temperatures. Perfect 90 degrees corners on the proof mass was successfully etched using a corner compensation design at etching temperature of 63 °C for KOH and 67.7 °C for TMAH with 25 wt% and 10.3 wt% concentration levels, respectively. Etching in TMAH required lower concentration level, thus making the etching process safer. However, TMAH required longer time to etch perfect convex corners compared to KOH. Nevertheless, both KOH and TMAH etchants have been successfully used to etch perfect convex corners by using the designed corner compensation mask.